Selected aspects of texts of the self-governmental consolidated statues of local law - Lewicki, Marek (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Practice of amending many times a statute gives rise to some problems in establishing binding contents of the statute. These problems should be eliminated by an institution of a consolidated text. This paper focuses on selected aspects of this legal institution with respect to statutes of local law. It explains regulations normalizing an obligation to announce these texts, their legal character as well as principles of eliminating errors occurring in them . It also emphasizes a necessity of due diligence when editing these texts in order to prevent consolidated texts from being against the binding law.